2022
DOI: 10.3390/ma15155312
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of ECAP Processing Conditions on Microstructural Evolution and Mechanical Properties of Pure Magnesium—Experimental, Mathematical Empirical and Response Surface Approach

Abstract: In this study, a quantitative evaluation approach was used to investigate how certain ECAP processing parameters affect the microstructural evolution, Vicker’s microhardness values and tensile properties of pure Mg. The ECAP processing parameters were number of passes, ECAP die channel angle and processing route type. The response surface methodology (RSM) technique was used to design 16 runs of the experiment using Stat-Ease design expert software. Billets of pure Mg were processed up to four passes of routes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…They outlined that the starting basal slip clutches the great majority of the deformation, while the subsequent passes involved the activation of non-basal slip systems and so required a lower amount of deformation energy [ 47 ]. Alateyah et al [ 84 ] generated a comprehensive statistical analysis of the effect of ECAP parameters on the grain size and mechanical properties of pure Mg. They reported that 2-Bc using an ECAP die with a channel angle of 120° was the optimum processing condition for increasing σu, whereas 4-C using an ECAP die with a channel angle of 120° was the optimum processing condition for improving the ductility.…”
Section: Resultsmentioning
confidence: 99%
“…They outlined that the starting basal slip clutches the great majority of the deformation, while the subsequent passes involved the activation of non-basal slip systems and so required a lower amount of deformation energy [ 47 ]. Alateyah et al [ 84 ] generated a comprehensive statistical analysis of the effect of ECAP parameters on the grain size and mechanical properties of pure Mg. They reported that 2-Bc using an ECAP die with a channel angle of 120° was the optimum processing condition for increasing σu, whereas 4-C using an ECAP die with a channel angle of 120° was the optimum processing condition for improving the ductility.…”
Section: Resultsmentioning
confidence: 99%
“…Meyer et al [ 96 ] and Agnew et al [ 97 ] reported similar improvement in the ductility of AZ31B, whereas they noticed a decrease in the YS while the UTS kept constant. Alateyah et al [ 98 ] generated a comprehensive statistical analysis for the effect of ECAP parameters on the tensile properties of pure Mg. Mostaed et al [ 24 ] achieved improvement in the EL by 30% of ZK60 alloy after ECAP processing through 4-passes at 150 °C. Naik et al [ 85 ] reported a similar trend for AM80 alloys.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, increasing the die angle up to 120° in both regions resulted in decreasing the hardness, which could be attributed to the decrease in the plastic strain [ 35 ]. Furthermore, increasing the number of passes resulted in hardness improvement, which could be argued to be the result of strain hardening [ 57 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…The obtained optimum values for channel angle and corner angles were 93.64° and 0°, respectively. Alateyah et al [ 57 ] used RSM, ANOVA, GA, and RSM-GA to optimize the ECAP parameters of pure Mg, and they reported that ECAP processing using a die with ϕ = 90° through 4-passes of route Bc was the most significant parameters in grain reining and Vicker’s microhardness values. Furthermore, ECAP processing using an ECAP die with ϕ = 120° through two passes of route Bc displayed the highest TS, while 4-passes of route C using the 120°-die showed the best D% at fracture.…”
Section: Introductionmentioning
confidence: 99%